Comparison of Battery Electrical Vehicles and Internal Combustion Engine Vehicles–Greenhouse Gas Emission Life Cycle Assessment - Vasco Vieira; Andresa Baptista; Adélio Cavadas; Gustavo F. Pinto; Joaquim Monteiro; Leonardo Ribeiro (Applied Sciences)
Battery electrical vehicle (BEV) ownership has increased in recent years. There is a general concern over the life cycle of the batteries used in such vehicles. This study provides a comprehensive overview of electric vehicles, encompassing their technical evolution, autonomy, and ownership. The analysis delved into the various types of batteries utilized in these vehicles, examining the composition of their constituent materials and the mechanisms underlying their operation. Additionally, it assessed their performance in terms of energy density storage, recharge capabilities, autonomy, and prospects. A critical evaluation of electric vehicles and their internal combustion engine vehicle (ICEV) counterparts, considering the Life Cycle Assessment (LCA) criterion, was conducted. The LCA criterion encompasses emissions during the entire lifecycle, from the “cradle” to the “tank” (WTT) and the “tank” until the end of its cycle (TTW). The findings of this study indicate that BEVs consistently outperformed ICEVs in terms of greenhouse gas (GHG) emissions in all the sizes of vehicles studied.